CORRELATION OF RISK-TAKING ATTITUDE AND INDIVIDUAL WELL-BEING IN INDONESIA - Gilang Ramadhan, Gusti
The study aims at investigating how risk-taking attitude affects individual well-being in Indonesia. The condition of individual well-being in Indonesia still requires attention. In the health sector, even though various health programs have been implemented by the government, there are still many individuals who do not have access to adequate health services. In the field of education, there are still many individuals in Indonesia who do not have access to proper education, and there are still many individuals in Indonesia who live below the poverty line (26.16 million people per March 2022). Individual risk-taking attitude (as a psychological factor and economic behavior) is closely related to various aspects of life including individual well-being. Human empowerment as part of the endogenous development concept emphasizes the importance of improving the ability of individuals and communities to take an active role in the development process. When individuals have a healthy and courageous risk-taking attitude, they tend to be better able to face challenges and take steps to improve their own well-being. This attitude can encourage active participation in economic, social, and political activities. We used datasets from the fifth wave of the Indonesian family life survey (IFLS) with observations of 22,333 individuals of 15 years old or older with risk-taking attitudes as independent variables. We used individual total consumption, comparison of food and non-food consumption, age-appropriate education level, chronic disease diagnosis, and tendency to depression as outcome variables. For analysis, we used probit as a baseline and used ivprobit, and eprobit regression as an attempt to deal with the endogeneity problem using an instrumental variable. The results of the regression coefficient show that there is a significant correlation between risk-taking attitudes and individual well-being in the dimensions of material living standards, education, and health. Individuals who are male, have higher education, and located in urban areas increase the likelihood of being more courageous in taking risks. Individuals also tend to respond to potential gains and losses in different ways. Based on the research findings, we recommend policy interventions to build a risk culture and act as a catalyst in encouraging the implementation of individual risk management.